The Effect of Electronic LKPD Teaching Materials on Student Learning Outcomes on PAI Material in High School - Safwandy Nugraha, Mulyawan; Mulyati, Yanti (Yayasan Mentari Madani, 2024)
This study aims to determine the effectiveness of Electronic LKPD teaching materials and invite students to be able to apply them. This research model is library-research, research data from primary sources and secondary data. This research uses a qualitative approach with a literature study method and then these data are processed by concept analysis. The conclusion of this research in PAI learning needs to build an atmosphere such as encouraging learning is very important to attract students' interest in absorbing and interpreting the lessons that have been delivered by educators. By contextualizing PAI material, it will make students' understanding more thorough and integrate it with other subjects that can be easily understood. When a student understands the material received, the educator can ensure that the student is able to contextualize the material. Educators' creativity and foresight to social and cultural conditions must be able to illustrate PAI material so that the material does not seem outdated and can be applied in appropriate circumstances and conditions.The results of the analysis stated that the Electronic LKPD teaching materials can help improve student learning outcomes in PAI materials. This is also to make it easier for students to understand the material and its implementation in daily life